Effect of milling activation of dry components on properties of foamed cement mortar in a two-stage manufacturing process - Janis Baronins; Andrei Shishkin; Vitalijs Lusis; Chiara Giosuè; Dmitri Goljandin; Iveta Novakova; Sofija Kekez; Aleksandrs Korjakins; Dmitrijs Gorelikovs; Pavels Gavrilovs (Case Studies in Construction Materials, 2025)
This study investigates the impact of high-energy milling on foamed cement mortar, which is crucial for its lightweight and insulating properties. The research uses a two-rotor disintegrator for milling cement, sand, and microsilica to evaluate the mechanical properties of foamed cement mortar produced with a high-speed homogenizer in a novel two-stage process. Comparisons are made between non-milled, single-milled, and double-milled individual components and mixtures with commercial binders. While energy consumption significantly increases after double-milling, immediate use of single-milled mixtures leads to enhanced compressive strength – 6.53 MPa for Portland-limestone cement and 9.95 MPa for white Portland cement. However, storing these mixtures for three days reduces their strength to 5.20 MPa and 6.63 MPa, respectively, due to reagglomeration. Milling reduced mortar strength, except for white Portland cement, which reached 132 MPa at 56 days. Microstructural analysis reveals finer particles and larger pores in samples made with milled mixtures, highlighting the importance of immediate use for optimal foamed cement mortar quality.